Metastable photo-induced superconductivity far above T c - Sambuddha Chattopadhyay; Christian J. Eckhardt; Dante M. Kennes; Michael A. Sentef; Dongbin Shin; Angel Rubio; Andrea Cavalleri; Eugene A. Demler; Marios H. Michael (npj Quantum Materials)
Abstract Inspired by the striking discovery of metastable superconductivity in K3C60 at 100K, far above T c = 20 K, we discuss possible mechanisms for long-lived, photo-induced superconductivity. Starting from a model of optically-driven Raman phonons coupled to inter-band electronic transitions, we develop a microscopic mechanism for photo-controlling the pairing interaction. Leveraging this mechanism, we first investigate long-lived superconductivity arising from the thermodynamic metastable trapping of the driven phonon. We then propose an alternative route, where the superconducting gap created by an optical drive leads to a dynamical bottleneck in the equilibration of quasi-particles. We conclude by discussing the implications of both scenarios for experiments that can be used to discriminate between them. Our work provides falsifiable explanations for the nanosecond-scale photo-induced superconductivity found in K3C60, while simultaneously offering a theoretical basis for exploring metastable superconductivity in other quantum materials.